Analysis Of Factors Influencing The Level Of Patient Satisfaction In Online Registration At Ngancar Community Health Center, Kediri District - Evi Sita Dewi; Sentot Imam Suprapto (Universitas STRADA Indonesia, 2021)
Patient assessment of health care services is based on patient experience. The aspect of patient experience can be interpreted as a treatment or action from a nurse that is or has been undergone, felt and borne by someone who uses health services. The purpose of this study was to analyze the influence of service quality and perception on the level of patient satisfaction in registering online at the Ngancar Health Center, Kediri Regency. The design of this research is observational quantitative research. with a cross-sectional approach with the focus of the research directed to analyze the influence of service quality and perception on the level of patient satisfaction in registering online at the Ngancar Health Center, Kediri Regency with a population of 72 respondents and a sample of 53 respondents taken using the Accidental Sampling technique. The findings showed that most respondents had a good category of service quality, as many as 27 respondents (50.9%). Most respondents had a good category of perception, as many as 28 respondents (52.8%). Most respondents had a satisfied category of satisfaction. as many as 30 respondents (56.6%). The results of the study using the Test Logistic Regression shows that with a p-value <0.05 then H 1 is accepted so it is concluded that simultaneously there is an influence of service quality and perception on the level of patient satisfaction in registering online at the Ngancar Health Center, Kediri Regency. Respondents are expected to provide input and constructive criticism so that the online registration service provided can be in accordance with expectations.